2014
DOI: 10.1002/2014ja020575
|View full text |Cite
|
Sign up to set email alerts
|

Wave normal angles of whistler mode chorus rising and falling tones

Abstract: We present a study of wave normal angles (θk) of whistler mode chorus emission as observed by Time History of Events and Macroscale Interactions during Substorms (THEMIS) during the year 2008. The three inner THEMIS satellites THA, THD, and THE usually orbit Earth close to the dipole magnetic equator (±20°), covering a large range of L shells from the plasmasphere out to the magnetopause. Waveform measurements of electric and magnetic fields enable a detailed polarization analysis of chorus below 4 kHz. When d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
85
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(100 citation statements)
references
References 59 publications
(90 reference statements)
13
85
0
Order By: Relevance
“…It corresponds to parallel resonant energies ∼ 1-3 keV. In the presence of the additional free energy brought by electron beams, inverse Landau damping (i.e., wave growth for ∂f /∂v > 0) may therefore allow very oblique lower-band chorus wave amplification about ∼ 2 • -8 • away from the resonance cone angle θ r , as in statistical observations from the THEMIS satellite (Taubenschuss et al 2014).…”
Section: Linear Growth Rates In Presence Of Temperature Anisotropy Ormentioning
confidence: 88%
See 3 more Smart Citations
“…It corresponds to parallel resonant energies ∼ 1-3 keV. In the presence of the additional free energy brought by electron beams, inverse Landau damping (i.e., wave growth for ∂f /∂v > 0) may therefore allow very oblique lower-band chorus wave amplification about ∼ 2 • -8 • away from the resonance cone angle θ r , as in statistical observations from the THEMIS satellite (Taubenschuss et al 2014).…”
Section: Linear Growth Rates In Presence Of Temperature Anisotropy Ormentioning
confidence: 88%
“…Comprehensive statistical investigations of high-resolution wave-forms of whistler-mode waves in the radiation belt Li et al 2011Taubenschuss et al 2014) have confirmed the presence of a significant population of high-amplitude (B w > 1 nT, E w > 50 mV/m) waves discovered by Cattell et al (2008) and Cully et al (2008). A noticeable portion of these waves are very oblique, with a large parallel electric field component E Taubenschuss et al 2014). In this review, we have shown that such waves can organize a fast transport of electrons in energy/pitch-angle space via the trapping mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Nevertheless, significant portions of the observed nonGaussian amplitude distributions of parallel and oblique waves do correspond to very high amplitudes. 2,19,21,34,63,66 When propagating through background plasma and magnetic field which are both inhomogeneous, such high-amplitude waves can interact with electrons in the nonlinear regime 25,31,48 when electron trajectories depend significantly on the wave field over time intervals long enough. 13,15 Such nonlinear interactions include particle trapping and nonlinear scattering (also called phase bunching).…”
Section: Introductionmentioning
confidence: 99%